Poverty and Environment: Social Participation in the Process of Transference of new technologies of the environment in Recibido: 09/04/2010 Aprobado: 10/06/2010 the community of Collanac, Lima - Verástegui Gonzales, Norma (2010)
The present study aims to determine the socioeconomic and cultural level of the population of the Plateau-Manchay and reconstruct the process of social participation of the common interlenguage against the transfer of the misttrap technology for the improvement of the environment in the area, it was mainly used the quantitative method in addition to the descriptive and analytical ones. The result of this survey allowed to produce two diagnoses (1996 and 2001) and a proposal of social participation model which can be replicated in other realities, adapting them according to external and internal context. Despite the adverse conditions of poverty and extreme poverty of the misttrap technology area, the population managed to take possession to more integrated, democratic, and social participation.